Taxing e-commerce in South Africa – A critical look at South Africa’s income tax provisions in relation to international trends - Takor, Ayuk Ndiep (University of the Witwatersrand, Johannesburg, 2023)
Global digitalisation continues to accelerate its impact on economies around the world, triggering changes which challenge the rules for taxing international business income. These challenges create opportunities for companies with activities in multiple jurisdictions to leverage on their technological capacities and capitalize on the absence of synergies between the tax systems of jurisdictions in which they operate, to optimise their tax burden, to the detriment of the markets in which their profits are generated. From a South African perspective, the growth and evolution of the digital economy therefore brings a primary concern to the forefront of the domestic fiscal agenda – how should digital activities be categorised for income tax purposes, and what are the elements necessary in order to build the appropriate taxing framework for these activities? A critical analysis of key international tax guidelines such as the OECD BEPS Action Plan, and a qualitative and comparative analysis of the approach adopted to the questions above by key jurisdictions such as the UK and Nigeria, shows that there are certain factors which have achieved global consensus on their key nature to taxing the digital economy, and are now international trends to note when defining the tax treatment of income from e-commerce. While South Africa’s current income tax laws are able to tax income earned by non-residents from sources within the Republic, the digitisation of business and increased sophistication of digital business models does not always allow for the apprehension or proper categorisation of this income for tax purposes. South African legislature needs to draw inspiration from theseinternational trends to build an appropriate framework for taxing income earned through the digital economy, while balancing a drive to generate fiscal revenue, with the need to stimulate domestic growth and attract foreign investment.
A research report submitted to the faculty of commerce, law, and management in partial fulfilment of the requirements for the degree of master of commerce ( specialising in taxation), University of the Witswatersrand, Johannesburg, 2023
Keywords: Global digitalisation; UCTD; International trends; Tax income; E-commerce; SDG-8: Decent work and economic growth